Cardiac high-energy phosphate metabolism in patients with aortic valve disease assessed by 31P-magnetic resonance spectroscopy. - Neubauer, S; Horn, M; Pabst, T; Harre, K; Strömer, H; Bertsch, G; Sandstede, J; Ertl, G; Hahn, D; Kochsiek, K (1997)
BACKGROUND: The purpose of this work was to determine the clinical and hemodynamic correlates of alterations in cardiac high-energy phosphate metabolism in patients with aortic stenosis and with aortic incompetence. METHODS: Fourteen volunteers, 13 patients with aortic stenosis, and 9 patients with aortic incompetence were included. Patients underwent echocardiography and left and right heart catheterization. 31P-MR spectra from the anterior myocardium were obtained with a 1.5 Tesla clinical MR system. RESULTS: Aortic stenosis and aortic incompetence patients had similar New York Heart Association (NYHA) classes (2.77 +/- 0.12 vs 2.44 +/- 0.18), ejection fractions (normal), left ventricular (LV) end-diastolic pressures, and LV wall thickness. In volunteers, phosphocreatine/adenosine triphosphate (ATP) ratios were 2.02 +/- 0.11. For all patients, phosphocreatine/ATP was significantly reduced (1.64 +/- 0.09; *p = 0.011 vs volunteers). Phosphocreatine/ATP decreased to 1.55 +/- 0.12 (*p = 0.008) in aortic stenosis, while in aortic incompetence, phosphocreatine/ATP only showed a trend for a reduction (1.77 +/- 0.12; p = 0.148). For all patients, phosphocreatine/ATP decreased significantly only with NYHA class III (1.51 +/- 0.09; *p = 0.001), but not with NYHA classes I and II (phosphocreatine/ATP 1.86 +/- 0.18). In aortic stenosis, phosphocreatine/ATP ratios decreased (1.13 +/- 0.03; *p = 0.019) only when LV end-diastolic pressures were > 15 mm Hg or when LV diastolic wall stress was > 20 kdyne cm-2 (1.13 +/- 0.03; *p = 0.024). CONCLUSIONS: For a similar clinical degree of heart failure in human myocardium, volume overload hypertrophy does not, but pressure overload does, induce significant impairment of cardiac high-energy phosphate metabolism. In aortic valve disease, alterations of high-energy phosphate metabolism are related to the degree of heart failure.